2021
DOI: 10.1007/s10552-021-01449-7
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of a culturally-appropriate, educational intervention to increase participation in cancer clinical trials among African Americans and Latinos

Abstract: Aim: Culturally-appropriate, educational programs are recommended to improve cancer clinical trial participation among African Americans and Latinos. This study investigated the effect of a culturally-appropriate, educational program on knowledge, trust in medical researchers, and intent for clinical trial participation among African Americans and Latinos in Middle Tennessee.Method: Trained community health educators delivered a 30-minute presentation with video testimonials to 198 participants in 13 town hall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Researchers have demonstrated the importance of culturally tailored education design to improve health outcomes and enhance diversity in clinical trials, which has significantly contributed to the field of health disparities ( 38 , 39 , 41 ). However, given the scarcity of culturally tailored community-based recruitment methodology for ADRD among older African Americans, this study provides evidence to support the potential utility of future culturally tailored community-based recruitment methods for ADRD clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated the importance of culturally tailored education design to improve health outcomes and enhance diversity in clinical trials, which has significantly contributed to the field of health disparities ( 38 , 39 , 41 ). However, given the scarcity of culturally tailored community-based recruitment methodology for ADRD among older African Americans, this study provides evidence to support the potential utility of future culturally tailored community-based recruitment methods for ADRD clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Cunningham-Erves et al (2021) examined the effect of a culturally tailored educational program to enhance participation in cancer trials among African Americans and Latinos. Results demonstrated that the culturally tailored curriculum increased willingness to participate in research and improved trust between the researchers and the community ( 41 ). This paper expands on the current literature around culturally tailored education by focusing on a disease that disproportionally impacts the African American community.…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria were as follows: (1) case studies, review articles, and studies focused only on identifying an inequity or disparity in cancer care. While educational programs to either increase knowledge, beliefs, and attitudes about cancer screening 16,17 or increase participation in clinical research trials 18 have been well-studied, we were specifically interested in methods or interventions that measured an impact on one or more cancer-related health equity metrics.…”
Section: Methodsmentioning
confidence: 99%
“…Given elevated disease burden and poorer cancer outcomes among the underserved, it is critical that trial participation disparities are investigated [7,9]. Moreover, recent literature indicates that implementation of patient-centered, culturally sensitive recruitment strategies tailored toward CCT engagement among underrepresented populations in cancer research have yielded positive implications for attenuating inequities in CCT participation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%